2017
DOI: 10.21037/tp.2017.10.04
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial aspects of diabetes management: dilemma of diabetes distress

Abstract: Diabetes mellitus (DM) is a debilitating chronic illness with complex pathophysiological, psychological, and quality of life (QoL) implications creating a constant state of turbulence. Some of these interconnections are apparent to healthcare providers and are easily addressed in a routine diabetic clinical care. However, a large number of these hidden factors that interplay with each other and impact on the physical outcomes of DM goes unnoticed by health care providers. This is a frustrating and lonely predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 34 publications
0
52
0
2
Order By: Relevance
“…An online survey found that almost one-fourth of the studied general Indian public had moderate to extreme depression [ 9 ]. People with diabetes have multiple psychosocial issues, which coupled with the psychological stressors of a pandemic, social distancing, lockdown, and quarantine creates an unsettling situation [ [10] , [11] , [12] , [13] ]. The prevalence of various mental disorders in people with DM is between 20% and 55%, depending on clinical and socio-demographic variables [ [14] , [15] , [16] ].…”
Section: Introductionmentioning
confidence: 99%
“…An online survey found that almost one-fourth of the studied general Indian public had moderate to extreme depression [ 9 ]. People with diabetes have multiple psychosocial issues, which coupled with the psychological stressors of a pandemic, social distancing, lockdown, and quarantine creates an unsettling situation [ [10] , [11] , [12] , [13] ]. The prevalence of various mental disorders in people with DM is between 20% and 55%, depending on clinical and socio-demographic variables [ [14] , [15] , [16] ].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes exposes people to both physical (cardiovascular diseases, neuropathy, diabetic foot, stroke, etc.) and psychological complications (e.g., depression and emotional distress); it also has a direct impact on several social aspects and, more generally, on daily life (due to, e.g., glycemic con-trol and changes in dietary habits and in lifestyle) [2][3][4][5]. Indeed, psychosocial factors seem to be, for diabetic patients, better predictors of relevant clinical outcomes (i.e., mortality and hospitalization) than other physiological indexes generally used to assess health status such as HbA 1C [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…When a diabetic patient is depressed, he/she often conducts self-destructive behaviors such as eating and drinking a lot, which cause the disease to get out of their control. [ 13 ] The results of the Egede et al . [ 14 ] study showed that depressed diabetics compared to nondepressed diabetics receive more prescriptions, use more outpatient care, and their care costs are 4.5 times higher.…”
Section: Discussionmentioning
confidence: 99%